The influence of post-processing software on quantitative results in 4D flow cardiovascular magnetic resonance examinations - Trauzeddel, Ralf F.; Müller, Maximilian; Demir, Aylin; Wiesemann, Stephanie; Daud, Elias; Schmitter, Sebastian; Viezzer, Darian; Hadler, Thomas; Schulz-Menger, Jeanette (Frontiers in Cardiovascular Medicine, 2024)
Background Several commercially available software packages exist for the analysis of three-dimensional cine phase-contrast cardiovascular magnetic resonance (CMR) with three-directional velocity encoding (four-dimensional (4D) flow CMR). Only sparse data are available on the impact of these different software solutions on quantitative results. We compared two different commercially available and widely used software packages and their impact on the forward flow volume (FFV), peak velocity (PV), and maximum wall shear stress (WSS) per plane. Materials and methods 4D flow CMR datasets acquired by 3 Tesla magnetic resonance imaging of 10 healthy volunteers, 13 aortic stenosis patients, and 7 aortic valve replacement patients were retrospectively analyzed for FFV, PV, and WSS using two software packages in six analysis planes along the thoracic aorta. Absolute (AD) and relative differences (RD), intraclass correlation coefficients (ICC), Bland–Altman analysis, and Spearman's correlation analysis were calculated. Results For the FFV and PV in healthy volunteers, there was good to excellent agreement between both software packages [FFV: ICC = 0.93–0.97, AD: 0.1 ± 5.4 ml (−2.3 ± 2.4 ml), RD: −0.3 ± 8% (−5.7 ± 6.0%); PV: ICC = 0.81–0.99, AD: −0.02 ± 0.02 ml (−0.1 ± 0.1 ml), RD: −1.6 ± 2.1% (−9.3 ± 6.1%)]. In patients, the FFV showed good to excellent agreement [ICC: 0.75–0.91, AD: −1.8 ± 6.5 ml (−8.3 ± 9.9 ml), RD: −2.2 ± 9.2% (−13.8 ± 17.4%)]. In the ascending aorta, PV showed only poor to moderate agreement in patients (plane 2 ICC: 0.33, plane 3 ICC: 0.72), whereas the rest of the thoracic aorta revealed good to excellent agreement [ICC: 0.95–0.98, AD: −0.03 ± 0.07 (−0.1 ± 0.1 m/s), RD: −3.5 ± 7.9% (−7.8 ± 9.9%)]. WSS analysis showed no to poor agreement between both software packages. Global correlation analyses revealed good to very good correlation between FFV and PV and only poor correlation for WSS. Conclusions There was good to very good agreement for the FFV and PV except for the ascending aorta in patients when comparing PV and no agreement for WSS. Standardization is therefore necessary.